2023
DOI: 10.3390/cancers15143677
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Novel EUS-FNB-Derived Organoid Co-Culture System for Drug Screening in Patients with Pancreatic Cancer

Simon Ezban Grützmeier,
Bojan Kovacevic,
Peter Vilmann
et al.

Abstract: Cancer-associated fibroblasts (CAFs) have been shown to impact the chemosensitivity of patient-derived tumor organoids (PDTOs). However, the published literature comparing PDTO response to clinical outcome does not include CAFs in the models. Here, a co-culture model was created using PDTOs and CAFs derived from endoscopic ultrasound-guided fine-needle biopsies (EUS-FNBs) for potential use in drug screening applications. Co-cultures were established, and growth was compared to monocultures using image metrics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Knoblauch M et al established direct 3D co-cultures of primary PDAC organoids and patient-matched CAFs to investigate the influence of stromal components on chemosensitivity ( Knoblauch et al, 2023 ). Similarly, Grützmeier SE et al developed a co-culture model using PDTOs and CAFs derived from endoscopic ultrasound-guided fine-needle biopsies (EUS-FNBs) for potential use in drug screening and molecular mechanisms unraveling involved in the chemoresistance-supporting role of the tumor stroma ( Grützmeier et al, 2023 ). In research reported by Zou et al, HCC-PDOs and PBMC are co-cultured with MSC and CAFs to construct HCC organoid-on-a-chip mimicking the original TME ( Zou et al, 2023 ).…”
Section: Application Of Organoids In Gi Tumorsmentioning
confidence: 99%
“…Knoblauch M et al established direct 3D co-cultures of primary PDAC organoids and patient-matched CAFs to investigate the influence of stromal components on chemosensitivity ( Knoblauch et al, 2023 ). Similarly, Grützmeier SE et al developed a co-culture model using PDTOs and CAFs derived from endoscopic ultrasound-guided fine-needle biopsies (EUS-FNBs) for potential use in drug screening and molecular mechanisms unraveling involved in the chemoresistance-supporting role of the tumor stroma ( Grützmeier et al, 2023 ). In research reported by Zou et al, HCC-PDOs and PBMC are co-cultured with MSC and CAFs to construct HCC organoid-on-a-chip mimicking the original TME ( Zou et al, 2023 ).…”
Section: Application Of Organoids In Gi Tumorsmentioning
confidence: 99%
“…In particular, organoids can be established in resected tissues before chemotherapy or after neoadjuvant chemotherapy to measure the response to anticancer drugs, which is useful for precision therapy, drug screening, and tumor biology research [48]. Recently, PDOs were generated using endoscopic ultrasound-guided fine-needle aspiration biopsies [46,[49][50][51][52] and utilized in co-culture systems for drug screening [51,52].…”
Section: Pancreatic Research Tools and Pancreatic Disease Modelsmentioning
confidence: 99%
“…In a recent feasibility study, authors were able to establish a co-culture using PDOs from a small amount of EUS FNB samples and cancer-associated fibroblasts (CAFs). Limitations like a high risk of contamination (blood as well as benign cells), compromising the yield of tissue available, the suboptimal number of needle passes, and unknown histopathological diagnoses before EUS TA can be obviated in future studies to improve the success rate [ 146 ].…”
Section: Recent Advancement In Eus Ta In Pancreatic Carcinomamentioning
confidence: 99%